The effects of aerobic exercise training on oxidant-antioxidant balance, neurotrophic factor levels, and blood-brain barrier function in obese and non-obese men - Roh, Hee-Tae; So, Wi-Young (Journal of sport and health science, 2017)
Purpose： The purpose of this study was to investigate the effects of obesity and aerobic exercise training on oxidant-antioxidant balance, neurotrophic factor levels, and blood-brain barrier （BBB） function. Methods： Ten non-obese healthy men （body mass index 〈 25 kg/m^2） and 10 obese men （body mass index 〉 25 kg/m^2） were included in the study. Both groups performed treadmill exercise for 40 min 3 times weekly for 8 weeks at 70% heart rate reserve. Blood samples were collected to examine oxidant-antioxidant balance （reactive oxygen species （ROS） and superoxide dismutase （SOD） activity levels）, neurotrophic factors （brain-derived neurotrophic factor （BDNF）, nerve growth factor, and glial cell line-derived neurotrophic factor levels）, and BBB function （S 100~ and neuron-specific enolase （NSE） levels） before and after exercise training. Results： The obese group showed significantly greater changes than the non-obese group in serum ROS （-0.46 ± 0.31 mmol/L vs. -0.10 ± 0.17 mmol/L,p = 0.005）, serum S1001] levels （-8.50 ± 5.92 ng/L vs. -0.78 ± 5.45 ng/L,p = 0.007）, and serum NSE levels （-0.89 ± 0.54 μg/L vs. -0.01 ± 0.74 μg/L,p = 0.007） after training. At baseline, the obese group showed significantly higher serum ROS and S 100β levels and significantly lower serum SOD activity and BDNF levels than the non-obese group （p 〈 0.05）. The obese group showed significantly lower serum ROS, S100β, and NSE levels and significantly higher serum SOD activity and BDNF levels after training compared with baseline （p 〈 0.05）. Conclusion： These results suggest that obesity can reduce serum neurotrophic factor levels and can induce BBB dysfunction. On the other hand, aerobic exercise can improve an oxidant-antioxidant imbalance in obese subjects and limit BBB dysfunction.